Prevalence of Geriatric Syndromes and the Need for Hospice Care in Older Patients of the Emergency Department: A Study in an Asian Medical Center - Ya-Ting Ke; An-Chi Peng; Yi-Min Shu; Min-Hsien Chung; Kang-Ting Tsai; Ping-Jen Chen; Tzu-Chieh Weng; Chien-Chin Hsu; Hung-Jung Lin; Chien-Cheng Huang (Emergency Medicine International)
Background. The prevalence of geriatric syndromes and the need for hospice care in the emergency department (ED) in Asian populations remain unclear. This study was conducted to fill the data gap. Methods. Using a newly developed emergency geriatric assessment (EGA), we investigated the prevalence of geriatric syndromes and the need for hospice care in older ED patients of a tertiary medical center between September 1, 2016, and January 31, 2017. Results. We recruited a total of 693 patients with a mean age of 78.0 years (standard deviation 8.2 years), comprising 46.6% of females. According to age subgroups, 37.4% of patients were aged 65–74 years, 37.4% were aged 75–84 years, and 25.2% were aged ≥85 years. The prevalence rates of geriatric syndromes were as follows: delirium (11.4%), depression (23.4%), dementia (43.1%), deterioration of activities of daily living (ADL) for <1 year (29.4%), vision impairment (22.2%), hearing impairment (23.8%), sleep disturbance (13.1%), any fall in <1 year (21.8%), polypharmacy (28.7%), pain (35.1%), pressure ulcer (5.6%), incontinence or retention (29.6%), indwelling device or physical restrain (21.6%), nutrition problem (35.7%), frequent use of medical resources (50.1%), lack of advance care planning (84.0%), caregiver problem (4.6%), socioeconomic problem (5.5%), and need for family meeting (6.2%). The need for hospice care was 11.9%. Most geriatric syndromes increased with advancing age except depression, sleep disturbance, polypharmacy, pain, nutrition problem, lack of advance care planning, caregiver problem, and socioeconomic problem. Conclusion. Geriatric syndromes and the need for hospice care were common in the older ED patients. Further studies about subsequent intervention for improving geriatric care are needed.